Immune-instructive polymers for modulating macrophage phenotype - Alromaihi, Reem (2024)
Background Medical devices, from implants to gene/drug delivery systems and biosensors, often elicit immune reactions ranging from transient inflammation to chronic inflammation and fibrosis, known as the foreign body reaction (FBR). These immune responses can lead to device failure and tissue damage, highlighting the need for biomaterials that not only avoid these reactions but actively guide positive immune interactions for tissue integration and healing. The role of macrophages, with their highly plastic nature, is critical in the orchestration of these immune responses, making them a focal point for biomaterial design aimed at minimising FBR and enhancing implant integration. High-throughput screening using polymer microarrays has been increasingly utilised to accelerate the discovery of new biomaterials. Previously, this strategy has identified acrylate and acrylamide polymers that can modulate the polarisation state of macrophages based on their expression of surface markers using fluorescent labels and microscopy. Unlike the macrophage ‘secretome’, surface marker expression only provides a partial insight into the macrophage functional phenotype. However, since conventional polymer microarrays do not have defined cell culture chambers for individual polymer spots, investigating the secretome in this format is not feasible.